EXPLORING INDONESIAN EFL PRE-SERVICE TEACHERS’ EXPERIENCES IN AI-ASSISTED TEACHING PRACTICUM: BENEFITS AND DRAWBACKS - Wulandari, Mega; Purnamaningwulan, Rina Astuti (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
The integration of Artificial Intelligence (AI) in educational settings is rapidly evolving, presenting both opportunities and challenges for pre-service English teachers. This case study explored three Indonesian EFL pre-service teachers’ experiences in using AI technologies and the implications for their pedagogical practices during teaching practicum. Several AI tools, namely ChatGPT, Copilot, Twee, and Quizizz AI, were used to help the pre-service teachers in planning, creating learning content, and assessing students. Data were collected from semi-structured interviews, reflective reports, and artifacts from the three Indonesian pre-service teachers majoring in English language education joining a teaching practicum program in a local school for 6 weeks. The qualitative data analysis revealed that the Indonesian EFL pre-service teachers saw three essential benefits of AI-assisted teaching practicum: (1) AI assists them with brainstorming and ideation process, (2) AI makes teaching preparation more time efficient, and (3) AI assists them in crafting tailor-made English materials for students. Meanwhile, they also addressed some challenges in the process, namely (1) overreliance, (2) ethical violation, and (3) fabricated and misleading contents.